Mafia and outlaw stories from Italian life and literature - Pickering-Iazzi, Robin (Toronto ; Buffalo : University of Toronto Press, 2007)
Mafia and Outlaw Stories from Italian Life and Literature takes a unique and intriguing approach to the subject of the Mafia, and offers informed judgements about its historical impact on Italian society and culture.
Introduction: Not the Sopranos-- viewing the Mafia and outlaws through Italian eyes -- The Gold key / Giovanni Verga -- An episode of brigandage (1855) / Carolina Invernizio -- The blessed Paulists (1909-10) / Luigi Natoli (William Galt) -- Testagrossa agrees (1911) / Giuseppe Ernesto Nuccio -- The hired killer (1928) / Grazia Deledda -- The carob tree (1993) / Maria Occhipinti -- Montelepre (1955) / Anna Maria Ortese -- Searching for Palermo (1990) / Amelia Crisantino -- The truvatura (1992) / Silvana La Spina -- The Mafia at my back (1991) / Livia De Stefani -- Testimonies: Maria Saladino, Felicia Impastato, Letizia Battaglia, Rita Atria.
Includes bibliographical references (pages 175-180).
Print version record.
JSTOR
Keywords: Mafia in literature; Outlaws in literature; Mafia -- Italy -- History; Women and the mafia -- Italy; Italian fiction -- 20th century -- Translations into English; Italian fiction -- 19th century -- Translations into English; Women -- Italy -- Biography; Crime in popular culture -- Italy; Hors-la-loi dans la littérature.; Mafia -- Italie -- Histoire; Femmes et mafia -- Italie; Femmes -- Italie -- Biographies; Criminalité dans la culture populaire -- Italie; FICTION -- General; SOCIAL SCIENCE -- Criminology; Crime in popular culture; Italian fiction; Mafia; Mafia in literature; Outlaws in literature; Women; Women and the mafia; Italy; 1800-1999; Computer network resources; Biographies; History; Translations